2014
DOI: 10.1182/blood-2013-06-510909
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 is a novel regulator of mouse neutrophil migration

Abstract: Key Points ATF3 inhibits lipopolysaccharide-driven CXCL1 production by airway epithelia. ATF3 controls neutrophil recruitment to the wild-type lung and chemotaxis in vitro via TIAM2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 42 publications
5
69
0
Order By: Relevance
“…ATF3 was shown to be important for neutrophil migration in the lungs via transrepression of CXCL1 chemokine (38). Another study reported that ATF3 functions as a novel negative regulator of neutrophil differentiation by modulating Ly6G expression (39).…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 was shown to be important for neutrophil migration in the lungs via transrepression of CXCL1 chemokine (38). Another study reported that ATF3 functions as a novel negative regulator of neutrophil differentiation by modulating Ly6G expression (39).…”
Section: Discussionmentioning
confidence: 99%
“…As CXCR2 ligands were particularly downregulated in airway epithelium, we investigated whether recombinant CXCL1, CXCL2, or CXCL5 could rescue impaired bacterial clearance in the ethanol group. Local delivery of recombinant CXCL1 and CXCL5 (doses used in previous studies [16][17][18]) but not CXCL2 significantly decreased bacterial burden compared to the ethanol group that received vehicle control (Fig. 6C).…”
Section: (Paired T Test) (B) Gene Expression Data From Panelmentioning
confidence: 98%
“…27 In neutrophils, ATF3 reduced expression of chemokines, such as C-X-C motif ligand 1 (CXCL1), but promoted neutrophil chemotaxis. 28 In primary human monocytes and macrophages, IFN-γ significantly induced ATF3 expression, which in turn bound to the promoter of matrix metalloproteinase 1 (MMP-1), reducing its transcription. 29 IFN-β induced ATF3 expression, which binds to a distal regulatory sequence of IFN-β to reduce its transcription.…”
Section: Role Of Atf3 In Immune Functionmentioning
confidence: 99%